Peran Strategis Dana Desa dalam APBN: Meningkatkan Kesejahteraan Masyarakat Desa - Ahmad Wahyudi Zein; Dhany Saputra Sembiring; Ema Julia Ningsih (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study uses a qualitative method to provide an in-depth description of the strategic role of village funds within the State Budget (APBN) in improving the welfare of rural communities. Village funds allocated by the central government aim to accelerate development, reduce regional disparities, and strengthen economic independence at the village level. This research examines the mechanisms of distribution, management, and utilization of village funds and relates them to welfare indicators such as income, access to basic services, and economic empowerment. The results show that when managed transparently, accountably, and with community participation, village funds can improve quality of life through infrastructure development, better education and health services, and the growth of micro and small enterprises. However, challenges such as weak capacity of village officials, corruption practices, and lack of supervision remain obstacles that must be addressed. Therefore, synergy between central and regional governments and the community is key to the successful implementation of village funds.